Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 4545 species occurrences available in GBIF matching the query: { "and" : [ "DatasetKey is Norwegian Species Observation Service", { "or" : [ "TaxonKey is Petromyzon marinus Linnaeus, 1758", "TaxonKey is Lampetra fluviatilis (Linnaeus, 1758)", "TaxonKey is Lampetra planeri (Bloch, 1784)", "TaxonKey is Lampetra japonica (Martens, 1868)", "TaxonKey is Rutilus rutilus (Linnaeus, 1758)", "TaxonKey is Leuciscus leuciscus (Linnaeus, 1758)", "TaxonKey is Leuciscus cephalus (Linnaeus, 1758)", "TaxonKey is Leuciscus idus (Linnaeus, 1758)", "TaxonKey is Phoxinus phoxinus (Linnaeus, 1758)", "TaxonKey is Scardinius erythrophthalmus (Linnaeus, 1758)", "TaxonKey is Aspius aspius (Linnaeus, 1758)", "TaxonKey is Tinca tinca (Linnaeus, 1758)", "TaxonKey is Alburnus alburnus (Linnaeus, 1758)", "TaxonKey is Blicca bjoerkna (Linnaeus, 1758)", "TaxonKey is Abramis brama (Linnaeus, 1758)", "TaxonKey is Carassius carassius (Linnaeus, 1758)", "TaxonKey is Carassius auratus (Linnaeus, 1758)", "TaxonKey is Cyprinus carpio Linnaeus, 1758", "TaxonKey is Gobio gobio (Linnaeus, 1758)", "TaxonKey is Leucaspius delineatus (Heckel, 1843)", "TaxonKey is Ictalurus nebulosus (Lesueur, 1819)", "TaxonKey is Esox lucius Linnaeus, 1758", "TaxonKey is Osmerus eperlanus (Linnaeus, 1758)", "TaxonKey is Salmo salar Linnaeus, 1758", "TaxonKey is Salmo trutta Linnaeus, 1758", "TaxonKey is Oncorhynchus mykiss (Walbaum, 1792)", "TaxonKey is Oncorhynchus gorbuscha (Walbaum, 1792)", "TaxonKey is Oncorhynchus keta (Walbaum, 1792)", "TaxonKey is Salvelinus alpinus (Linnaeus, 1758)", "TaxonKey is Salvelinus fontinalis (Mitchill, 1814)", "TaxonKey is Salvelinus namaycush (Walbaum, 1792)", "TaxonKey is Coregonus lavaretus (Linnaeus, 1758)", "TaxonKey is Coregonus albula (Linnaeus, 1758)", "TaxonKey is Thymallus thymallus (Linnaeus, 1758)", "TaxonKey is Lota lota (Linnaeus, 1758)", "TaxonKey is Gasterosteus aculeatus Linnaeus, 1758", "TaxonKey is Pungitius pungitius (Linnaeus, 1758)", "TaxonKey is Cottus gobio Linnaeus, 1758", "TaxonKey is Cottus poecilopus Heckel, 1837", "TaxonKey is Myoxocephalus quadricornis (Linnaeus, 1758)", "TaxonKey is Perca fluviatilis Linnaeus, 1758", "TaxonKey is Sander lucioperca (Linnaeus, 1758)", "TaxonKey is Gymnocephalus cernuus (Linnaeus, 1758)", "TaxonKey is Lepomis gibbosus (Linnaeus, 1758)" ] }, "HasCoordinate is TRUE", "Country is Norway" ] } The dataset includes 4545 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001939-200127171203522/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences